Uncovering online lifestyle segments using the Motivation Sequence Model - Ang, Yvonne Su Ming (2018)
Online lifestyle market segmentation provides essential understanding of the marketplace and consumer lifestyle. Being able to identify and differentiate consumers can directly contribute to the structure and efficacy of market strategies. However, limited work has been done so far, mostly drawing on work in the early 2000s. Since then, the marketplace has transformed quickly, and in particular, there is a need to investigate the use theoretical model specification and update the approach to online lifestyle market segmentation. In this research, the Motivation Sequence Model (MSM) functions as a means to understand consumer lifestyle from a goal-directed behaviour viewpoint. Underpinned by the macro-framework, the Theory of Basic Human Values and the Unified Theory of Acceptance and the Use of Technology 2 (UTAUT2) represent the motivational process of the consumer. Given this scenario, this research sets out to 1) identify consumer segments for online lifestyle market segmentation, 2) examine the Value → Behaviour link, 3) examine the effects of Values on the framework and, 4) examine the effects of Personality as a moderator. Results from an online survey of 403 online consumers using judgemental sampling revealed: 1) three consumer segments; namely, Resolute, Established and Spontaneous consumers; 2) the affirmation of the Value → Behaviour link, where values act as antecedents for Effort Expectancy, Facilitating Conditions, Hedonic Motivation and Habit, which then influence Behavioural Intention and Purchase Behaviour; 3) the impact of Self-Direction, Security, Hedonic Motivation and Achievement on UTAUT2 reflects on the multiple value influence on one behaviour and; 4) Emotional Stability to be not significant as a moderator. The research concludes by discussing the theoretical and practical implications, limitations and future directions for online lifestyle market segmentation.